Development of Intermediate Media for Snakes and Ladders Multiplication and Division for Understanding Mathematics Class III State Primary School 1 Banjar Tengah - Astika Dewi, Made Sri; Nurgiansah, T Heru (CV. Rayyan Dwi Bharata, 2025)
The facilities formulated regarding this analysis contain visual learning intermediaries which include game boards, question cards related to multiplication and division, material cards, dice, and pawns (students). This research aims to develop learning media and determine the feasibility, practicality and effectiveness of this method. The development method used in this research is the development model A D D I E,